Does movement games impact on increasing sports participation, fundamental movement skill and life satisfaction of students disabilities? - Dimyati, Akhmad; Junaidi, Junaidi; Wiradihardja, Sudradjat; Dlis, Firmansyah; Mahardhika, Dhika Bayu; Dermawan, Dikdik Fauzi; Monterrosa Quintero, Armando; Gil-Espinosa, Francisco Javier; Setiawan, Edi (University of Las Palmas de Gran Canaria, 2023)
This study aims to investigate the effect of movement games programs on increasing sports participation, fundamental movement skill and life satisfaction of students with disabilities. This study adopted a mixed methods type. The participants were 40 students from the Karawang city. The quantitative instruments involved Sport Participation Scale, Test of Gross Motor Development 2 and the Satisfaction with Life Scale while the qualitative instruments used in-depth interviews. Quantitative analysis using SPSS and nonparametric analysis using the Mann-Whitney U test were used to test the differences in the three dependent variables.Qualitative statistical analysis was carried out qualitatively thematically. First, in the quantitative study showed that there was no difference between sports participation, movement skill and life satisfaction in the experimental and control groups before the experiment (p>0.05). Second, there was a difference between sports participation, fundamental movement skill and life satisfaction after the experiment (p<0.05). Third, the qualitative findings showed diverse perceptions from students.
Keywords: Ejercicio físico - Aspectos psicológicos; Juegos; Personas con discapacidad; Movement games; Sports participation; Fundamental movement skill; Life satisfaction